Comparative evaluation of funduscopy, PCR and serology in the diagnosis of ocular toxoplasmosis at ECWA Eye Hospital, Kano - Biodun Bintu Adebakin; Mayor Orezime Atima; Ugbede Idakwo; Jamilu Abubakar Bala; Alhasan Sharif Abdullahi; Auwal Bello Muhammad; Jah Douglas Pam; Emeka John Dingwoke; Florence Olufunke Darda (BMJ Open Ophthalmology)
Objective Ocular toxoplasmosis, caused by Toxoplasma gondii, is a significant cause of posterior uveitis and vision impairment globally. Accurate diagnosis is essential to prevent retinal damage and optimise treatment. This study aimed to compare three diagnostic methods funduscopy, serology (ELISA), and PCR in detecting ocular toxoplasmosis in patients at ECWA Eye Hospital, Kano, Nigeria.Methods and analysis A total of 264 patients suspected of having ocular toxoplasmosis were enrolled. Funduscopy was performed to identify retinal lesions typical of T. gondii. Serological analysis was conducted using ELISA to detect anti-Toxoplasma IgG antibodies. Additionally, PCR was used to confirm the presence of T. gondii DNA in blood samples. The results from these methods were compared with assess their sensitivity, specificity and diagnostic value.Results Funduscopy detected T. gondii in 25.4% (67/264) of the patients, while ELISA showed a higher detection rate of 36.7% (97/264). PCR, the most specific method, confirmed infection in only 3.8% (10/264) of cases, with 60% (6/10) of these being male and 40% (4/10) female. T. gondii detected had 196 base pairs. The study found that ELISA had the highest sensitivity (90.0%) but lower specificity (64.9%), whereas funduscopy showed high specificity (74.4%) but low sensitivity (20.0%). PCR had the highest specificity but a low detection rate, emphasising its role in confirming diagnosis.Conclusion Although ELISA and funduscopy detected more positive cases, PCR remains the gold standard for confirming T. gondii infection due to its high specificity. In resource-limited settings like ECWA Eye Hospital, combining serology and PCR offers a practical approach for improving diagnostic accuracy and ensuring timely treatment of ocular toxoplasmosis.